Efficacy of peracetic acid in postharvest disease control and quality preservation of banana (Musa spp.) (Agroindustrial Science, 2026)
Banana (Musa spp.) can lose more than 20% postharvest due to fungal rots, creating a need for packing-friendly disinfection options. This study aimed to determine the efficacy of peracetic acid (PAA) to reduce crown-rot severity and its effect on ripening in bananas from Piura, Peru. Fruit was immersed for 10 min in 0 (control), 40, 80, 120, and 150 ppm PAA; for each concentration, 32 fruits were processed (8 from each of four sampling zones). Samples were incubated in humid chambers (22 °C; 85% – 90% RH) and disease severity was scored on an ordinal scale (1–5). Data were analyzed with Kruskal–Wallis and Dunn’s multiple comparisons (α = 0.05). Severity differed among treatments (χ² = 75.42, df = 4, p < 0.001): 80, 120 and 150 ppm significantly reduced severity versus 0 and 40 ppm, with no difference between 120 and 150 ppm. No phytotoxicity symptoms were observed during storage, and 150 ppm showed the greatest ripening delay (greener fruit by the end of the evaluation period). Fusarium oxysporum, Thielaviopsis musarum and Lasiodiplodia theobromae were isolated from controls. Overall, 120 – 150 ppm (especially 150 ppm) appears as operational doses to reduce postharvest rots and extend shelf life without compromising fruit appearance.
Keywords: banana; Musa; postharvest diseases; rots; disinfection; shelf; shelf life; ripening; peracetic acid